Generating and measuring the anisotropic elastic behaviour of Co thin films with oriented surface nano-strings on micro-cantilevers - Madurga Vicente; Vergara José; Favieres Cristina (Nanoscale Research Letters, 2011)
Abstract In this research, the elastic behaviour of two Co thin films simultaneously deposited in an off-normal angle method was studied. Towards this end, two Si micro-cantilevers were simultaneously coated using pulsed laser deposition at an oblique angle, creating a Co nano-string surface morphology with a predetermined orientation. The selected position of each micro-cantilever during the coating process created longitudinal or transverse nano-strings. The anisotropic elastic behaviour of these Co films was determined by measuring the changes that took place in the resonant frequency of each micro-cantilever after this process of creating differently oriented plasma coatings had been completed. This differential procedure allowed us to determine the difference between the Young's modulus of the different films based on the different direction of the nano-strings. This difference was determined to be, at least, the 20% of the Young's modulus of the bulk Co. PACS: 62.25.-g; 81.16.Rf; 68.60.Bs; 81.15.Fg; 68.37.Ef; 85.85.+j